2015
DOI: 10.1111/cts.12297
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement in Neurological Clinical Trials Design: A Conference Summary

Abstract: Objectives: The conference objectives included educating patients and advocates about clinical trials, educating the clinical research community about patient perspectives on participating in clinical trial design, and identifying strategies to increase participation in clinical trial design for neurological disorders. Design: Observations were noted during a 1-day conference attended by patients, patient advocates, clinical trial staff, and investigators. The conference offered didactic sessions, small, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…Partnership with a geographic or patient community can be used to share the rationale and methods of biomedical research, develop research agendas, and design feasible trials (3). Patient advocacy groups, such as the American Kidney Fund, National Kidney Foundation, NephCure Kidney International, and Polycystic Kidney Disease Foundation, may serve as powerful partners in convening or participating in community engagement activities.…”
Section: Community Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Partnership with a geographic or patient community can be used to share the rationale and methods of biomedical research, develop research agendas, and design feasible trials (3). Patient advocacy groups, such as the American Kidney Fund, National Kidney Foundation, NephCure Kidney International, and Polycystic Kidney Disease Foundation, may serve as powerful partners in convening or participating in community engagement activities.…”
Section: Community Engagementmentioning
confidence: 99%
“…Patient advocacy groups, such as the American Kidney Fund, National Kidney Foundation, NephCure Kidney International, and Polycystic Kidney Disease Foundation, may serve as powerful partners in convening or participating in community engagement activities. Research sponsors, networks, and health systems conduct forums for open dialogue, health fairs, and other educational events, where community and research team members have the opportunity to collaborate to improve community awareness and participation in biomedical research (3,4). The Rare Disease Clinical Research Network website provides opportunities for patients to enroll in disease-specific patient contact registries.…”
Section: Community Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient engagement in clinical trials includes participation in identifying unmet research needs; selecting and prioritizing outcome measures; collaborating on study design, execution, analysis, and interpretation; and translating, disseminating, and implementing clinical trial results in the community. 43 , 53 Such patient engagement has been recommended and implemented across multiple therapeutic areas, including cardiology, 13 infectious disease, 6 neurology, 4 and oncology. 2 , 7 Studies of the impact of patient engagement in clinical trials have reported that the participation of patients can provide important contributions to study feasibility, rigor, and relevance 19 and can also have financial value by contributing to the avoidance of protocol amendments and the improvement of enrollment, adherence, and retention.…”
Section: Trials Transitions and Translationsmentioning
confidence: 99%
“…Research on medication adherence can be applied more systematically to ensure adequate medication adherence in these trials [33]. Another challenge of health research is the engagement of participants in longitudinal trials and observational cohort studies [34]. Principles of behavioral and social sciences such as altruism, persuasion, and motivation can be applied to improve the sustained engagement of participants in research.…”
Section: Implementation Of Behavioral and Social Science Findings In mentioning
confidence: 99%